Common spaces in the days of isolationism. Outline of the interdisciplinary research programme = Wspólne przestrzenie w czasach izolacjonizmu. Zarys interdyscyplinarnego programu badawczego - Bazuń, Dorota; Kwiatkowski, Mariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents an outline of the interdisciplinary research program. The program is a response to the growing isolationist tendencies. The term "isolationism" refers here to a wide variety of forms and expressions of aspiring to diversity by social communities, due to the search for solutions for problems which affect these groups. Both phenomena from the sphere of politics and economy or culture can be found to be expressions of isolationism. The authors propose to carry out an interdisciplinary, international research on the ability to create good and lasting connections between social groups, cultures, institutions, or "common space" of encounter, dialogue and cooperation.
Keywords: izolacjonizm; wspólna przestrzeń; kapitał społeczny; relacje społeczne; isolationism; community; space; social capital; social relations